The Impact of Case-Based Education on the Development of Nursing Students' Clinical Reasoning Skills in Managing Critical Illnesses: A Pilot Randomized Controlled Trial. - Birge, Ayşegül Öztürk; Kutlutürkan, Sevinç (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2024)
Background: Nursing students require the development of clinical reasoning (CR) skills to deliver safe and effective care. Aim: This study aimed to determine the effect of case-based education on the development of CR skills among nursing students in managing critical illnesses. Methods: The study was conducted from January 20 to June 30, 2021, utilizing a pilot randomized controlled trial design. Twenty-two volunteer students were assigned to either the experimental or control groups through simple randomization. Data were collected using a Student Information Form, the Clinical Reasoning Case Form (CRCF), the Student Satisfaction with Education Questionnaire, and a Form for Views on Education. The data were analyzed using frequency values, Fisher's exact test, paired/independent samples t-test, Cohen's d coefficient for effect size, intention-to-treat (ITT) analysis, and covariance analysis. Results: The intervention and control groups were similar in terms of descriptive characteristics (P>0.05), and no significant difference was found between the groups in the pretest scores of the CRCF (P=0.351). In the intervention group, the posttest CR scores significantly increased following the education (P=0.015) with a large effect size [d=0.88 (-1.72-0.02)]. ITT analysis was conducted as one student from the control group did not complete the posttest. The results of the per-protocol and ITT analyses were similar. According to covariance analysis, the pretest scores did not affect posttest scores (P=0.155, η2=0.109). This study was registered on ClinicalTrials.gov with the number NCT05504824. Conclusion: Case-based education was found to be effective in enhancing the CR skills of nursing students in critical illnesses.